Interfacial characteristics and mechanical asymmetry in Al2024 matrix composites containing Fe-based metallic glass particles - He, Tianbing; Lu, Tiwen; Ciftci, Nevaf; Uhlenwinkel, Volker; Chen, Weiping; Nielsch, Kornelius; Scudino, Sergio (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Controversy regarding the possible effects of interfacial reaction between matrix and reinforcement has recently aroused in the field of aluminum matrix composites reinforced with metallic particles. In this study, Al2024 matrix composites containing Fe-based glass particles were heat treated to investigate the interfacial microstructure and the resulting effects on the mechanical behavior. The results reveal that a submicron sized Al7Cu2Fe intermetallic phase is formed at the particle-matrix interface during solid solution treatment and the thickness of intermetallic layer increases with increasing temperature and holding time. The formation of the intermetallic phase reduces the amount of Cu available for the precipitation hardening of the matrix, consequently decreasing the strength of the composites. Furthermore, the formation of the intermetallic layer weakens the particle-matrix interface bonding strength, resulting in failure of the composites by particle debonding, which significantly deteriorated the tensile properties. Tension-compression (T/C) asymmetry of the composites is caused by the difference in damage evolution as a response to compressive or tensile loads. The composites containing large glass particles showed aggravated T/C asymmetry, and the asymmetry increased with the advancing of the interfacial reaction. Our work indicates that the formation of intermetallic compounds larger than submicron size at the interface is detrimental to the mechanical properties of aluminum matrix composites reinforced with metallic particles.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Aluminum matrix composite (AMC); Interfacial reaction; Intermetallic phase; Metallic glass (MG); Tension-compression asymmetry